Doses de fósforos nas características agronômicas e teor de ácido cianídrico em cultivares de mandioca - Nascimento, Fernanda Ramalho do (2016)
Phosphorus (P), although essential to energy supply to plant metabolism, is little studied in manioc. In this sense, the objective of this work was to evaluate the phosphorus doses effect on yield and quality of manioc roots of the cultivars Alciolina and Amazonas, in Savannah environment in Boa Vista, Roraima. The experiment was carried out in a randomized complete block design, in a subdivided plots scheme, being allocated five doses of phosphorus (0, 45, 90, 180 e 360 kg ha-1 of P2O5) in the plot and both cultivars (Alciolina e Amazonas) in subplots. Twelve months after planting, three plants were harvested in useful area of the plot to analyze the following variables: plant height, quantity of stems per plant, yield of fresh shoot matter, quantity of roots per plants, commercial root quantity, diameter and average length of the commercial root, average fresh mass of commercial roots, average fresh mass of commercial roots per plant, tuber root yield, harvest index and hydrocyanic acid content (HCN) in the cortex and pulp of the root. Phosphorus doses positively affect the agronomic characteristics of the cultivars Alciolina and Amazonas, being described, in general, by quadratic model. The yield of tuberous roots reached was 84 and 52 t ha-1 for cv. Amazonas and cv. Aciolina, with doses of maximum technical efficiency of 208 and 191 kg ha-1 of P2O5, respectively. The content of HCN, both in the pulp and in the cortex, tended to decrease due to greater availability of phosphorus. The cultivar Amazonas was more productive and showed greater efficiency in use of phosphorus on Roraima’s Savannah. Key words: Phosphate fertilization; Cultivar Aciolina.; Cultivar Amazonas; Manihot esculenta; Production of manioc; Savannah of Roraima.